2014
DOI: 10.1097/dcr.0000000000000210
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Staging CT Thorax in Patients With Colorectal Cancer

Abstract: Pulmonary metastasis is relatively rare in colorectal cancer, and staging CT of the thorax may not be mandated in low-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…1 in hogan et al 1 ), and the data support the fact that t3/t4 tumors with lymphovascular invasion and lymph node metastasis possess a higher chance of liver and lung metastases. 1 in hogan et al 1 ), and the data support the fact that t3/t4 tumors with lymphovascular invasion and lymph node metastasis possess a higher chance of liver and lung metastases.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…1 in hogan et al 1 ), and the data support the fact that t3/t4 tumors with lymphovascular invasion and lymph node metastasis possess a higher chance of liver and lung metastases. 1 in hogan et al 1 ), and the data support the fact that t3/t4 tumors with lymphovascular invasion and lymph node metastasis possess a higher chance of liver and lung metastases.…”
supporting
confidence: 58%
“…To the Editor-in response to hogan et al, 1 we compliment them on their retrospective observational study in relation to the role of preoperative staging Ct thorax in patients with colorectal cancer. the study population is well representative of the united Kingdom and ireland.…”
mentioning
confidence: 99%
“…These thoughts have been echoed in studies by Quyn et al [24] and Hogan et al [25], who demonstrated that intermediate nodules in patients with small localized primary CRC (i.e. These thoughts have been echoed in studies by Quyn et al [24] and Hogan et al [25], who demonstrated that intermediate nodules in patients with small localized primary CRC (i.e.…”
Section: Discussionmentioning
confidence: 96%
“…While ESMO guidelines suggest a CT scan of the abdomen and pelvis, without chest imaging, NCCN recommends contrast enhanced imaging of the chest [32,33]. In patients without hepatic metastasis, the rate of isolated pulmonary metastasis is extremely low at 1.4-6.3%, suggesting a relatively low yield for chest imaging [34][35][36]. A meta-analysis of 5873 patients demonstrated that although 9% of patients will be found to have an indeterminate nodule on chest imaging, only 10.8% of these will turn out to be metastatic colorectal metastasis, once again indicating a relatively low yield in the face of extensive work up that will be undertaken by many patients to evaluate indeterminate findings [37].…”
Section: Historical Overviewmentioning
confidence: 99%